DEGRADASI KOMUNITAS MANGROVE KALIMANTAN SELATAN AKIBAT PROSES DESALINASI PERAIRAN PESISIR - Eka Iriadenta (Fish Scientiae, 2019)
This study was to examine the process of desalination of coastal waters in South Kalimantan resulting in decreased quality of coastal habitat. Data input for research included time-series primary data of salinity values, derived from observation stations have been set. This research is based on grounded research methods to get the facts and comparison analysis through field observation and relevant data sources, including primary and secondary data, both qualitative and quantitative, as well as the approach to landscape approach using remote sensing data.The results showed that the phenomenon of coastal water desalination give effect to the fragility of coastal communities, especially mangroves, thus impacting derivatives of more vulnerability to degradation processes that occur on the coast of South Kalimantan. The research results can used as the basic of integrated coastal zone management.